Biomechanical factors critical for performance in the men's javelin throw - Morriss, C.; Bartlett, R. (Sports Medicine, 1996)
In the men's javelin event the athlete throws an 800g implement into a 40 degrees sector. The objective is to throw as far as possible. Compared with most other throwing implements, the javelin is relatively aerodynamic. Even so, the most important release parameter is still the release speed. Maximising this parameter gives the athlete the best chance of attaining success in the event. For an elite thrower, as much as 70% of the release speed of the javelin is developed in the last 0.1 second. As such, the movements of throwers during this period and immediately preceding it have received attention from researchers. It would appear that a thrower's body position at the instant of final foot strike, his ability to transfer momentum between the lower body and the upper body during the delivery, and coordination of the working body segments in the most effective manner are linked to his success in the event. This paper reviews the most important biomechanical research on the men's javelin throw and highlights findings such as these which may improve the understanding of how elite javelin throwers achieve success.